2006
DOI: 10.1016/j.ijfoodmicro.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food system conditions on N-acyl-l-homoserine lactones production by Aeromonas spp.

Abstract: t c o n c e n tr a t io n s o n A H L p r o d u c t i o n w a s d e t e r m i n e d in e i g h t A . h y d r o p h il a a n d o n e A . c a v ia e s tr a in . A d d iti o n a ll y a q u a n t ita tiv e s t u d y o f C 4 -H S L p r o d u c t io n b y A . h y d r o p h ila s tr a i n 5 1 9 u n d e r d if f e r e n t c o n d i tio n s w a s p e r f o r m e d . P o s i t i v e r e s u lt s w e r e f o u n d in t h e A H L in d u c tio n a s s a y f o r s o m e A e r o m o n a s s tr a i n s in c u l tu r e s in L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…In another study, all clinical tested strains of A. hydrophila ( n = 20) and Aeromonas sobria ( n = 2) produced either C4-HSL and C6-HSL or both, including 10 strains that produced an additional AHL, a putative N-pentanoyl homoserine lactone (C5-HSL; Chan et al, 2011). Other studies showed similar results, e.g., A. caviae YL12 (Table 3), although additional AHLs were not systematically characterized (Bruhn et al, 2005; Morgan-Sagastume et al, 2005; Medina-Martínez et al, 2006; Schwenteit et al, 2011; Chong et al, 2012; Huang et al, 2012; Chu et al, 2013; Ochiai et al, 2013; Lim et al, 2014; Zeng et al, 2014). The HPLC data confirmed results obtained with bioassays (Table 3).…”
Section: Quorum Sensing Systems In Aeromonasmentioning
confidence: 64%
“…In another study, all clinical tested strains of A. hydrophila ( n = 20) and Aeromonas sobria ( n = 2) produced either C4-HSL and C6-HSL or both, including 10 strains that produced an additional AHL, a putative N-pentanoyl homoserine lactone (C5-HSL; Chan et al, 2011). Other studies showed similar results, e.g., A. caviae YL12 (Table 3), although additional AHLs were not systematically characterized (Bruhn et al, 2005; Morgan-Sagastume et al, 2005; Medina-Martínez et al, 2006; Schwenteit et al, 2011; Chong et al, 2012; Huang et al, 2012; Chu et al, 2013; Ochiai et al, 2013; Lim et al, 2014; Zeng et al, 2014). The HPLC data confirmed results obtained with bioassays (Table 3).…”
Section: Quorum Sensing Systems In Aeromonasmentioning
confidence: 64%
“…The phenotypes include luminescence, conjugation, nodulation, swarming, sporulation, bio-corrosion, antibiotic production and most importantly biofilm formation (Nelson et al, 2007;Coenye et al, 2007;Kapellos et al, 2007;Wang et al, 2007) and the expression of virulence factors such as lytic enzymes, toxins, siderophores and adhesion molecules (De Kievit and Iglewski, 2000;Whitehead et al, 2001;De Windt et al, 2003). Therefore, studying the biosynthesis, reactivity, and degradation of N-acyl homoserine lactones and other quorum-sensing signals is of value not only for fundamental cellular processes, but also for important medicinal, environmental, agricultural, and industrial applications (Lamo Marin et al, 2007;), such as treating cystic fibrosis pneumonia (to prevent aggravation of biofilm growth on lungs), maintaining factory equipment in constant contact with water or developing transgenic plants with improved disease-resistance (Costerton et al, 1999;Fray et al, 1999;Winzer and Williams, 2001;Bi et al, 2007;Medina-Martinez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case with the niches present in food ecosystems, where the role of cell-cell communication has only recently received attention from food microbiologists, despite the fact that a growing body of evidence has been collected suggesting that bacterial food spoilage may also be regulated by QS systems (1,112). So far, few studies have investigated the influence of food system conditions on autoinducer signal production by foodborne pathogens (9,17,70,79,80) and the influence of these QS signals on the survival/growth of pathogenic bacteria in foods (9,115). Soni et al (116,117), for example, reported that the survival and virulence expression of a luxS mutant strain of Escherichia coli O157:H7 was enhanced in the presence of autoinducer-2 (AI-2).…”
Section: Bacterial Communicationmentioning
confidence: 99%
“…Short-chain AHLs are generally diffusible throughout the bacterial membrane, while long-chain AHLs seem to be actively transported in and out of the cells via efflux and influx systems (133). Several factors may influence the concentration and type (i.e., the length and substitution of the C-3 of the acyl chain) of AHLs, including temperature, pH, NaCl, growth medium, inoculum size, and bacterial growth phase (36,76,77,79,142).…”
Section: Intraspecies Cell-to-cell Communicationmentioning
confidence: 99%
See 1 more Smart Citation